An analysis of performance factors in sprint distance triathlon - Anta, R. C.; Turpin, J. A. P. (Journal of Human Sport & Exercise, 2007)
Triathlon is a combined endurance sport, which includes back-to-back swimming, cycling and running, always in that order and with total time measurements including the transition between events. According to the rules, sprint distance is always the shortest, and the one in which there are most events (0.750 km, 20 km, 5 km). Determining performance factors is a must in order to optimize training in any sports event; however, the various distances in this sport lead to different analyses. The purpose of this paper is to determine the performance factors in sprint distance triathlon, by reviewing the data supplied by the literature. In the cycling event, the performance factors are greatly dependent on whether drafting is permitted or not. In our study, the main factors have been found to be: raising the anaerobic threshold to the highest percentage with respect to the individual`s VO2max, producing and eliminating high lactate values, and developing a good specific technique for crawl swimming.